Autophagy Induced by Tumor Necrosis Factor α Mediates Intrinsic Apoptosis in Trophoblastic Cells. (May 2014) - Cha, Hyun-Hwa; Hwang, Jae Ryoung; Kim, Hyo-Youn; Choi, Suk-Joo; Oh, Soo-young; Roh, Cheong-Rae
To investigate the interconnection of apoptosis and autophagy in trophoblastic cells, we treated JEG-3 cells with tumor necrosis factor α (TNF-α) after transfecting LC3 or Beclin 1 or calpain small interfering RNA (siRNA), which blocks cleavage of autophagy-related gene 5 (Atg5) into N-terminal truncated Atg5 (tAtg5), a mediator between apoptosis and autophagy, and assessed the changes in LC3-II, caspase 9, caspase 3, and tAtg5. We also assessed the TNF-α-induced changes in LC3-II, caspase 9, and caspase 3 in primary trophoblasts from term placentae after transfecting siRNA for LC3 or Beclin 1. In both types of cells, transfection of LC3 or Beclin 1 siRNA significantly attenuated TNF-α-induced increases in LC3-II and activations of caspase 9 and caspase 3. There was significant abrogation of TNF-α-induced expression of tAtg5 after transfection with LC3 or Beclin 1 siRNA. Moreover, transfection with calpain siRNA significantly decreased TNF-α-induced changes in caspase 3 and caspase 9 in addition to tAtg5 in JEG-3 cells. Our data suggest that TNF-α-induced autophagy mediates intrinsic apoptosis, probably through tAtg5, in trophoblastic cells.